WHY NOTCH GEOMETRY MATTERS FOR STRUCTURAL AND AUTOMOTIVE APPLICATIONS: A NUMERICAL SIMULATION - Muflikhun, Muhammad Akhsin; Putro, Ardi Jati Nugroho; Chua, Alvin Y.; Santos, Gil Nonato C. (Jurnal Rekayasa Mesin, 2025)
In structural and automotive systems, notches—whether from manufacturing defects or in-service damage—often act as critical stress concentrators that compromise component integrity. This study provides a comprehensive simulation-based assessment of how different notch geometries affect the mechanical behavior of cold-rolled SPCC steel under tensile loading. Seven U-shaped notch variants were modeled according to ASTM E8M standards and evaluated using finite element analysis to determine von Mises stress, safety factor, and displacement patterns across five key regions. The findings reveal a clear correlation between notch diameter and failure risk: specimens with smaller notches (≤1 mm) exhibited von Mises stress exceeding 700 MPa and safety factors as low as 0.32, indicating early failure potential, whereas larger notches (≥6 mm) maintained stress levels below 250 MPa and safety factors above 1.0. This research offers practical design insights for engineers working with SPCC in automotive brackets, chassis, and thin-walled enclosures—highlighting the importance of avoiding sharp or undersized notches. The results support safer, more efficient design practices by providing predictive benchmarks and visual references that can aid in optimizing structural performance during early-stage development or finite element validation.